1974
DOI: 10.1177/002221947400700106
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Analysis of Classroom Behaviors of Children with Learning Disabilities

Abstract: This study was designed to measure taskoriented and social behavior of learning disabled and normal children in the classroom. Using an Interaction Process Analysis, the classroom behaviors of children were coded for five days over a fivemonth period. Results indicate that the learning disabled children spent significantly less time engaged in attending behavior for a variety of school subjects and that learning disabled children had different interpersonal relationships with teachers and peers than did compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(62 citation statements)
references
References 12 publications
4
55
2
1
Order By: Relevance
“…It has also been noted that this relationship has been reported for children at all grade levels, from the primary grade levels through college (McCandless & Evans, 1973;Adeniran, 1985;Salawu, 1991). Academic success and positive self-concept have also been shown to be positively correlated in Black and Hispanic children (Vasquez, 1974;Borovetz, 1975); in mentally retarded children (Tolor, 1974;Meyers, 1976); in physically handicapped childrefi (Byran, 1974;Cafferston, 1977); in sensory impaired children (^cMakin, 1976); and in learning disabled pupils (Seaman, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been noted that this relationship has been reported for children at all grade levels, from the primary grade levels through college (McCandless & Evans, 1973;Adeniran, 1985;Salawu, 1991). Academic success and positive self-concept have also been shown to be positively correlated in Black and Hispanic children (Vasquez, 1974;Borovetz, 1975); in mentally retarded children (Tolor, 1974;Meyers, 1976); in physically handicapped childrefi (Byran, 1974;Cafferston, 1977); in sensory impaired children (^cMakin, 1976); and in learning disabled pupils (Seaman, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Brophy and Good ( 1970) found that teachers demanded better performance from students they identified as high achievers and, additionally, they more frequently provided praise to those students for their performance when compared with the perceived low achievers. Bryan (1974) also found differences in the nature of interactions between learning disabled students and their teacher and their non-5 learning disabled peers and the teacher. The data from this study indicate that as much time was spent interacting with the teacher by both populations, but the learning disabled students were more likely to be ignored by the teacher; when they did receive attention, it was more likely to be of a helping nature than that received by their nonhandicapped peers.…”
Section: Peer-social Interactionsmentioning
confidence: 91%
“…N onhandicapped students have been reported to be less responsive to initiatives from handicapped peers than from their nonhandicapped peers. Bryan (1974) found that while handicapped children were as likely to initiate interaction with their peers, they were more likely to be ignored by them when compared with the nonhandicapped. Gottlieb and Davis ( 1973) found that when nonhandicapped students were given the choice of handicapped or nonhandicapped peers to serve as game partners, they were more likely to choose the nonhandicapped students.…”
Section: Peer-social Interactionsmentioning
confidence: 95%
See 1 more Smart Citation
“…This system was developed to enable an observer to analyze the interaction of a small group. Investigations of classroom interacton using the Bales' system suggest that the system is sensitive to variations in the quality of teacher-student interaction (Bryan, 1974;Bryan & Wheeler, 1972).…”
Section: Instrume Ntsmentioning
confidence: 99%